Dog Remains from Devon Island, N.W.T.: Archaeological and Osteological Evidence for Domestic Dog Use in the Thule Culture - Park, Robert W. (ARCTIC, 1987)
A collection of dog bones recovered from a Thule culture site at Porden Point, Devon Island, N.W.T., was found to include abundant evidence of trauma consistent with the dogs have been repeatedly struck in the facial area. The proportional representation of bones found suggests that the Porden Point dogs ultimately formed part of the diet there. A survey of historical and ethnographic accounts of the treatment of dogs by various Inuit groups indicates that the beating of dogs to discipline them was quite common, although evidence from other sources suggests that this type of behaviour is related more to the realities of dog keeping anywhere rather than to Inuit culture in particular. The evidence from other sources suggests that this type of behaviour is related more to the realities of dog keeping anywhere rather than to Inuit culture in particular. The evidence concerning the use of dogs in the diet among the various Inuit groups suggests that this varied greatly. Detailed descriptions of the types of trauma found on the Porden Point skulls are provided, in the hope that it may prove possible to identify similar evidence from earlier cultures where the nature of dog use is less certain.Key words: dogs, Thule culture, Devon Island, archaeology, faunal osteology Une collection d'os de chiens découvertes à un emplacement de culture Thulé à la pointe Porden dans l'île Devon (T. du N.-O.), contenait d'abondantes preuves de traumatismes semblant toutes indiquer que les chiens avaient été frappés de façon répétée sur le devant de la tête. Les proportions des différents os qu'on a trouvés nous permettent de penser que les chiens de la pointe Porden finissaient par former une partie de l'alimentation de la population locale.Une étude des relevés historiques et ethnographiques sur le traitement des chiens par divers groupes inuit, révèle qu'il était assez courant de battre les chiens pour les faire obéir. D'autres sources cependant nous fournissent des preuves qui laissent supposer que ce type de comportement est plus ...